Finite difference formulation of shape detection using Poisson's equation - Siti Hajar Azizan (Institute of Engineering Mathematics, Universiti Malaysia Perlis, 2017)
The main objective of this study is to predict the shape of detection shape. In order to achieve the main objective, the following sub-objectives will be carried out ; to discretize 2D Poisson's equation using FDM ; to develop numerical algorithm and procedure for solving 2D Poisson's equation ; to test and compare efficiency of numerical solution with 2D test dataset that includes geometric shapes.